2005
DOI: 10.1128/iai.73.7.4423-4426.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Recognition ofN-Formylmethionine Peptides Is a General Characteristic of H2-M3-Restricted CD8+T Cells

Abstract: H2-M3-restricted CD8؉ T cells can exhibit cross-reactivity to different bacterially derived N-formylmethionine peptides. The extent of this promiscuity is unclear. We deleted the nonredundant fMIVTLF epitope and found that Listeria monocytogenes still primed fMIVTLF-specific T cells. Thus, cross-reactivity appears to be a more general characteristic of H2-M3-restricted T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been shown that some H2-M3-restricted LMspecifi c CTLs are cross-reactive with antigens derived from a variety of Gram-positive and Gram-negative bacteria (29). In addition, deletion of H2-M3-restricted epitopes from LM does not prevent the priming of H2-M3-restricted T cells with specifi city for the deleted epitope, suggesting that promiscuous antigen recognition may be a feature common to many H2-M3-restricted T cells (30)(31)(32). The promiscuous recognition and cross-reactivity to common environmental bacteria may lead to the priming and expansion of LM-reactive H2-M3-restricted T cells in "naive" animals, resulting in increased precursor frequency as well as a "primed" state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some H2-M3-restricted LMspecifi c CTLs are cross-reactive with antigens derived from a variety of Gram-positive and Gram-negative bacteria (29). In addition, deletion of H2-M3-restricted epitopes from LM does not prevent the priming of H2-M3-restricted T cells with specifi city for the deleted epitope, suggesting that promiscuous antigen recognition may be a feature common to many H2-M3-restricted T cells (30)(31)(32). The promiscuous recognition and cross-reactivity to common environmental bacteria may lead to the priming and expansion of LM-reactive H2-M3-restricted T cells in "naive" animals, resulting in increased precursor frequency as well as a "primed" state.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited polymorphism of H2-M3 molecules, several distinct Lm -derived peptides containing N-formyl-methionine have been shown to induce CD8 + T cell responses [ 153 , 154 , 155 ], with fMIGWII being the major immunodominant epitope during Lm infection [ 156 ]. H2-M3-restricted CD8 + T cells express promiscuous antigen receptors which enable them to broadly recognize N-formylated peptides produced by Lm [ 157 , 158 , 159 ].…”
Section: Non-classical H2-m3-restricited Cd8 T Cell Responsementioning
confidence: 99%